2008
DOI: 10.1074/jbc.m710218200
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Mechanism and Structural Model of ADP-forming Acetyl-CoA Synthetase from the Hyperthermophilic Archaeon Pyrococcus furiosus

Abstract: In Archaea, acetate formation and ATP synthesis from acetylCoA is catalyzed by an unusual ADP-forming acetyl-CoA synthetase (ACD) (acetyl-CoA ؉ ADP ؉ P i % acetate ؉ ATP ؉ HS-CoA) catalyzing the formation of acetate from acetyl-CoA and concomitant ATP synthesis by the mechanism of substrate level phosphorylation. ACD belongs to the protein superfamily of nucleoside diphosphate-forming acyl-CoA synthetases, which also include succinyl-CoA synthetases (SCSs). ACD differs from SCS in domain organization of subuni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
45
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 38 publications
7
45
0
Order By: Relevance
“…The predicted beta-subunit of at least one of the putative acetyl-CoA synthetases contained a conserved histidine residue typical of well characterised acetyl-CoA synthetases that specifically form acetate and differentiate them from other structurally related succinyl-CoA synthetases (Bräsen et al, 2008). DEH-J10 may therefore gain ATP by substrate-level phosphorylation during the conversion of acetyl-CoA to acetate (McInerney et al, 2007;Bräsen et al, 2008).…”
Section: Acetyl-coa Synthetasesmentioning
confidence: 99%
See 1 more Smart Citation
“…The predicted beta-subunit of at least one of the putative acetyl-CoA synthetases contained a conserved histidine residue typical of well characterised acetyl-CoA synthetases that specifically form acetate and differentiate them from other structurally related succinyl-CoA synthetases (Bräsen et al, 2008). DEH-J10 may therefore gain ATP by substrate-level phosphorylation during the conversion of acetyl-CoA to acetate (McInerney et al, 2007;Bräsen et al, 2008).…”
Section: Acetyl-coa Synthetasesmentioning
confidence: 99%
“…Most of the top BLASTP hits for these predicted proteins were to proteins from the archaeal genera Pyrococcus and Thermococcus, which are known to catalyse the one-step formation of acetate from acetyl-CoA with the concomitant phosphorylation of ADP to ATP (Bräsen et al, 2008). The predicted beta-subunit of at least one of the putative acetyl-CoA synthetases contained a conserved histidine residue typical of well characterised acetyl-CoA synthetases that specifically form acetate and differentiate them from other structurally related succinyl-CoA synthetases (Bräsen et al, 2008). DEH-J10 may therefore gain ATP by substrate-level phosphorylation during the conversion of acetyl-CoA to acetate (McInerney et al, 2007;Bräsen et al, 2008).…”
Section: Acetyl-coa Synthetasesmentioning
confidence: 99%
“…A mechanism comparable to the mechanism of the SCSs was presumed for the ACDs (20). A study based on sequence, biochemical, and mutational analyses identified a highly conserved and functional relevant His residue within the beta subunit of the ACDs (20). Of note, the SCS enzymes do not contain a comparable His residue.…”
mentioning
confidence: 99%
“…Of note, the SCS enzymes do not contain a comparable His residue. Thus, an extension of the mechanism by a fourth step was suggested for the ACD1 from Pyrococcus furiosus (20). Here, the second His residue is thought to serve as an additional intermediate, which gets phosphorylated transiently during the enzymatic reaction and subsequently transmits the phosphoryl moiety onto the bound NDP.…”
mentioning
confidence: 99%
See 1 more Smart Citation